2003
DOI: 10.1016/s0195-668x(03)00309-9
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis in the elderly: clinical, echocardiographic, and prognostic features

Abstract: In this largest series of elderly patients with IE, IE in elderly carries specific features when compared with younger patients, although the echographic characteristics and embolic risk are similar. The overall mortality rate in elderly patients is higher than in younger, but the mortality in operated patients is low and similar than that of younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
2
19

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 19 publications
10
73
2
19
Order By: Relevance
“…The germs encountered in our study were the same for the young and the old patients. Conversely, some authors found some germs related to acute IE of elderly patients [4,7]. Particularly, we did not find in our study, a higher streptococcus bovis rate for elderly patients, in spite of the higher neoplasm rate in this class of age.…”
Section: Hospital Mortalitycontrasting
confidence: 99%
See 2 more Smart Citations
“…The germs encountered in our study were the same for the young and the old patients. Conversely, some authors found some germs related to acute IE of elderly patients [4,7]. Particularly, we did not find in our study, a higher streptococcus bovis rate for elderly patients, in spite of the higher neoplasm rate in this class of age.…”
Section: Hospital Mortalitycontrasting
confidence: 99%
“…Overall mortality younger and older patients [4,7]. The germs encountered in our study were the same for the young and the old patients.…”
Section: Hospital Mortalitymentioning
confidence: 52%
See 1 more Smart Citation
“…It can reach as high as 25% of cases in some specific groups of patients, such as patients developing endocarditis after hematopoietic stem cell transplantation [19]. Multivalvular location is independent of age [20,21] and no predisposing factors could be identified from the French cohort.…”
Section: Epidemiologymentioning
confidence: 99%
“…Basierend auf den Erfahrungen spezialisierter Zentren ist bei frühem operativem Eingreifen v. a. im Bereich der Atrioventrikularklappen (aber auch bei der Aortenklappe) häufig ein rekonstruktives Vorgehen möglich ohne die Notwendigkeit eines vollständigen Klappenersatzes [12]. Hierbei ist das Alter des Patienten nicht als eine Indikationseinschränkung für ein chirurgisches Vorgehen zu bewerten, wie auch Ergebnisse eigener Analysen zeigen [13].…”
Section: Prinzip Und Methodsenunclassified